Zakat Para Youtuber dalam Pandangan Hukum Islam - Ahmad Hujaj Nurrohim (Indonesia, 2019)
Zakah of YouTubers. Besides being a medium of entertainment and information, YouTube is currently one of the jobs. This article provides answers to the income problems of YouTubers. First, identify YouTuber income from the standpoint of Islamic law. Second, the pros and cons of the amount of zakat that must be excluded from their income Zakat Para YouTuber. Selain menjadi media hiburan dan informasi, YouTube saat ini menjadi salah satu lapangan pekerjaan. Artikel ini memberikan jawaban terhadap masalah penghasilan para YouTuber.Pertama, mengidentifikasi penghasilan YouTuber dari sudut pandang hukum Islam. Kedua, pro-kontra besaran zakat yang wajib dikeluarkan dari penghasilan mereka.